2022
DOI: 10.5267/j.ijdns.2021.12.003
|View full text |Cite
|
Sign up to set email alerts
|

The impact of social commerce on online purchase intention: The mediation role of trust in social network sites

Abstract: This research aimed to investigate the impact of social commerce on online purchase intention. The mediation role of trust in social network sites between social commerce and online purchase intention was explored. Dataset obtained from 467 Jordanian users of social network sites. PLS-SEM was conducted for analysis purposes. The findings reveal that social commerce and trust in social network sites directly affect online purchase intention. The findings have additionally shown that trust in social network site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…It was also found that purchase intention is significantly influenced by the relevance attributed to advertising, which allowed us to corroborate the second research hypothesis. These results are in line with the studies by Aloqool and Alsmairat (2022) according to which consumers tend to shop online when they consider that the advertising presented by the brand meets their needs and expectations.…”
Section: Discussionsupporting
confidence: 91%
“…It was also found that purchase intention is significantly influenced by the relevance attributed to advertising, which allowed us to corroborate the second research hypothesis. These results are in line with the studies by Aloqool and Alsmairat (2022) according to which consumers tend to shop online when they consider that the advertising presented by the brand meets their needs and expectations.…”
Section: Discussionsupporting
confidence: 91%
“…Generally, previous research has shown a positive relationship between trust and behavioral intention in several contexts (e.g., trust in online vendors [34], health product consumption [33], social commerce [35], willingness to provide information [31], and relationship intention [30]). Similarly, Bart et al [36] claimed a strong positive relationship between online trust and behavioral intention.…”
Section: Trust and Intentionmentioning
confidence: 99%
“…This is an open access article under the CC BY SA license (https://creativecommons.org/licenses/by-sa/4.0/) Aloqool & Alsmairat (2022) Social commerce and trust on social networks impact online purchase intent.…”
Section: Published By University Of Airlanggamentioning
confidence: 99%